Use of biomarkers for diagnosis and treatment of sepsis = Uso de biomarcadores en el diagnóstico temprano y el tratamiento de la sepsis - Jessica María Londoño Agudelo; Fabián Alberto Jaimes Barragán; Natalia Andrea Hoyos Vanegas; César Daniel Niño Pulido (Iatreia, 2013)
Background: Sepsis is a very complex clinical phenomenon in both its definition and pathophysiology. So far its diagnosis has been based only on clinical symptoms and signs together withthe results of some laboratory tests. However, efforts are being done to find biomarkers that are able to identify sepsis or rule it out, and to serve as guide for treatment. Objective: This review describes the most thoroughly studied biomarkers of sepsis and their potential use, as well as the experience achieved in Medellín, Colombia, with research in this field. Methods: A search on this subject matter was carried out in PubMed, and a critical analysis was done of the most relevant papers found including those published in Colombia.